Isolated lipstick-like ulceration of the ileocecal valve: A hallmark of cytomegalovirus colitis - Fady Daniel,; Nohra Ghaoui,; Walid R. Karaoui,; Bassel-Zein Sabatto,; Ibrahim Khalifeh,; Jean El-Cheikh, (Turkish Journal of Gastroenterology, 2020)
Cite this article as: Daniel F, Ghaoui N, Karaoui WR, Sabatto BZ, Khalifeh I, El-Cheikh J. Isolated lipstick-like ulceration of the ileocecal valve: A hallmark of cytomegalovirus colitis. Turk J Gastroenterol 2020; 31(3): 274-5.